Beneficial Effects of Access to a Disability Sports Facility on Mental and Physical Health of Patrons. - Cabador, Joy; Cottingham, Mike; Galanga, Alyson (Palaestra, 2022)
Given complex health conditions, people with disabilities would greatly benefit from receiving the proper tools to actively maintain health and wellness (Duarte Brito et al., 2016). Effects of the COVID-19 pandemic caused temporary closures of several U.S. public facilities, therefore creating an environment of complete absence of adaptive-designated recreational facilities. The purpose of this study was to establish the impact of an adaptive-specific facility on the physical and mental health of patrons who utilize the facility by comparing results of an open-facility vs. closed-facility. This study took place at an adaptive-designated recreational facility in a metropolitan, urban area in the Southern, US. Researchers surveyed 60 patrons with physical disabilities and impairments, who participated in structured sport programming, activity classes, or utilized the center in any capacity. Tests showed the mental health median differences between facility- closed and facility-open were statistically significant improvements, and the difference in physical health scores between the two facility status categories to be statistically significant improvements.